Fast Growth of the Logarithmic Derivative With Applications to Complex Differential Equations - Abdelhak Kara, Mohamed; Belaïdi, Benharrat (Sarajevo Journal of Mathematics, 2024)
In this paper, we give some estimates on the growth of the logarithmic derivative of meromorphic functions by considering the concept of $φ$-order. We discuss their relationship with the growth of solutions of certain complex differential equations.